2007
DOI: 10.1038/modpathol.3800740
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of mammalian sterile20-like kinase 1 in colorectal cancer

Abstract: Mammalian Sterile20-like kinase 1 (Mst1) is a member of the yeast Ste20-related kinase family known to be involved in the process of apoptosis initiated by a variety of stimuli. The aim of this study was to determine the prognostic significance of Mst1 expression in colorectal cancer. A series of 1197 mismatch-repair-proficient colorectal cancers retrieved from a tissue microarray were randomized into two study groups. On the first group (n ¼ 599) receiver operating characteristic curves were used to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 37 publications
5
66
1
Order By: Relevance
“…Similar to YAP overexpression, ablation of the Hippo pathway components Mer and Sav and double knockout of Mst1/2 in mice result in liver enlargement and tumor formation characteristic of HCC and cholangiocarcinoma (CC) (Zhou et al, 2009;Benhamouche et al, 2010;Lee et al, 2010;Lu et al, 2010;Song et al, 2010;. Aberrant Mst1/2 and Lats1/2 expression is observed in human cancers (Hisaoka et al, 2002;Jimé-nez-Velasco et al, 2005;Takahashi et al, 2005;Jiang et al, 2006;Minoo et al, 2007;Seidel et al, 2007;Cho et al, 2009;Zhou et al, 2009). Lats2 is also found mutated in human mesothelioma cell lines and non-small cell lung cancer (Strazisar et al, 2009;Murakami et al, 2011).…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 99%
“…Similar to YAP overexpression, ablation of the Hippo pathway components Mer and Sav and double knockout of Mst1/2 in mice result in liver enlargement and tumor formation characteristic of HCC and cholangiocarcinoma (CC) (Zhou et al, 2009;Benhamouche et al, 2010;Lee et al, 2010;Lu et al, 2010;Song et al, 2010;. Aberrant Mst1/2 and Lats1/2 expression is observed in human cancers (Hisaoka et al, 2002;Jimé-nez-Velasco et al, 2005;Takahashi et al, 2005;Jiang et al, 2006;Minoo et al, 2007;Seidel et al, 2007;Cho et al, 2009;Zhou et al, 2009). Lats2 is also found mutated in human mesothelioma cell lines and non-small cell lung cancer (Strazisar et al, 2009;Murakami et al, 2011).…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 99%
“…Mutations of the pathway components, such as NF2, WW45 and MOB1, have been linked to several types of human cancers (Tapon et al, 2002;Lai et al, 2005;Asthagiri et al, 2009). Downregulation of MST1/2, LATS1/2 and MOB1 has been observed in human sarcomas and various cancers (Hisaoka et al, 2002;Jiménez-Velasco et al, 2005;Takahashi et al, 2005;Kosaka et al, 2007;Minoo et al, 2007;Seidel et al, 2007). The main output of the Hippo pathway is to suppress the function of YAP by regulating its nuclear translocation and stability.…”
Section: Overview Of the Hippo Pathwaymentioning
confidence: 99%
“…By contrast, miR-18a knockdown in nude mice was demonstrated to decrease prostate tumor growth and induce apoptosis (16). STK4 is a proapoptotic protein that was identified as a tumor suppressor in cancer cells (31,32). Therefore, inhibition of The results of the current study demonstrated that the expression of peripheral blood miR-18a was significantly higher in patients with PC than in BPH patients and healthy control individuals.…”
Section: Discussionmentioning
confidence: 55%